Novel High-Gain Narrowband Waveguide-Fed Filtenna using Genetic Algorithm - Mahdi Ghorbani; Habib Ghorbaninejad (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Filtenna is an antenna with filtering feature. There are many ways to design a filtenna. In this paper, a high-gain narrowband waveguide-fed aperture filtenna has been proposed and designed. A patterned plane, which is designed using genetic algorithm has been used at the open end of the waveguide fed, mounted on a conducting ground plane. To design the patterned pattern, magnetic field integral equation of the structure has been derived, so it has been solved using method of moments. The proposed filtenna has been simulated with HFSS that confirms the results obtained by method of moments. Finally, an unprinted dielectric as a superstrate has been used to enhance the gain of the filtenna. The filtenna bandwidth is 1.76% (160 MHz)  which has the gain of 15.91 dB at the central frequency of 9.45 GHz.